If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3x + 13 = y Reorder the terms: 13 + x + 3x = y Combine like terms: x + 3x = 4x 13 + 4x = y Solving 13 + 4x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 4x = -13 + y Combine like terms: 13 + -13 = 0 0 + 4x = -13 + y 4x = -13 + y Divide each side by '4'. x = -3.25 + 0.25y Simplifying x = -3.25 + 0.25y
| 2x^2-6x-3=sqrt(4x+9) | | 6y=8x+12 | | (x=7)/6=x/3 | | (y-4)/3=(2-y)/3 | | =-4xy(7xy) | | =-4xy(-10xy) | | x-2/3=16/15 | | 2/7x-3=3/9x-5 | | =3x(m+n+y-z) | | k/2-k/5-k/6=2 | | -4/11-(-7/11) | | 4t^2+t-50=0 | | 3a/2-5=1 | | 2=2.5(R+0.05) | | Z=8-4 | | -5.7x(x+9.2)+4.1=3.4-6.9x | | 24=(100/x) | | 2w+2l=184 | | 3x=3x-8 | | 56+5=61 | | 0.35x+0.05(16-x)=0.10(-28) | | 6(3w-8)=42 | | 3(x+1)=18-6(x+1) | | -2(d+8)=20 | | -2(x)-4(y)=-8 | | Y^(1/x)=0 | | 81^(1/x)=0 | | 81^(1/x) | | (1x)/(81)=0 | | 2x-2(23/7)=7 | | 2(23/7)=7 | | 6+8y=30 |